Strategi Implementasi Sistem Manajemen Keselamatan Konstruksi Berdasarkan Peraturan Menteri Pekerjaan Umum dan Perumahan Rakyat Nomer 10 Tahun 2021 - Farida, Ery; Sholihah, Qomariyatus; Andarini , Sri; Natsir , M. Halim (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2024)
The aim of this research is to determine the factors that constitute strengths, weaknesses, opportunities and threats in the implementation of K3. The analytical tool used is SWOT analysis. SWOT analysis is carried out in several stages, namely Internal Factor Assessment, External Factor Assessment, creating a SWOT matrix, SWOT Score Calculation, SWOT Analysis Diagram and Internal and External Factor Matrix. The results are 1) Based on the SWOT analysis diagram, it is stated that the strategy to improve the implementation of occupational safety and health in the DPRKP and Cipta Karya Buildings in East Java Province that has been carried out so far is to support an aggressive strategy. 2) Based on the matrix of internal factors and external factors, it is known that the company can be efficient in the various strategies it implements. Companies can also collaborate with other service providers to provide K3 training for construction workers. However, with the condition of the company being in a downsizing cell, the company needs to downsize its investment, so it needs to implement a survival strategy. If linked to alternative strategies formulated through the SWOT matrix, then the alternative strategy that is closely related to survival strategy is the WO strategy alternative. Therefore, the alternative strategy that needs to be implemented by the company is an alternative WO strategy which consists of: (1) developing company work standards in accordance with government regulations regarding K3, (2) providing strict sanctions against construction workers who violate the rules, and (3) improve the flow of accident investigations and reporting.